French Rococo ébénisterie in the J. Paul Getty Museum - Wilson, Gillian, 1941-2019; Heginbotham, Arlen; Chasen, Jessica; Desmas, Anne-Lise (Getty Publications virtual library., 2021)
"Catalogue of the Rococo ébénisterie furniture in the collection of the J. Paul Getty Museum"--